CHANGES OF MORPHOMETRIC CHARACTERISTICS OF A HEARTAT EXPERIMENTAL DYSLIPOPROTEIDEMIA - Shevchuk, T.I.; Piskun, R.P.; Vasenko, T.B. (World of Medicine and Biology, 2017)
Rampant development of cardiology and cardiosurgery, application of various diagnostic techniques in clinical practice and sophistication of surgical manipulations on the heart requires a detailed study of morphological features of the heart and its structures not only in the age aspect of normal cardiac status, but also in various pathological conditions, including violation of lipid exchange. Study objective. The morphometric assessment of special features of structural reconstruction of coronary arteries in experimental dislipoproteinemia (EDLP). Materials and methods. The study involved 28 male rabbits of "chinchilla" breed weighing from 3.0 to 4.7 kg. Five animals composed an intact group free from any external influence. The state of experimental dislipoproteinemia was modeled according to the classical method by M.M. Anichkov, which meant that the rabbits were kept on an atherogenous diet for 3 months, fed with cholesterol in a dose of 0.5 g/kg of body weight. The microscopic sections of the left ventricle were stained with hematoxylin and eosin. The morphometry of coronary arteries was carried out using S.V. Shormanov method. We studied two groups of intramural vessels: the regular (outer diameter - 51 - 125 microns) and smaller ones (outer diameter - 26 - 50 microns). For that purpose, we measured the cross-section area of the arteries, the area of a lumen, the area of vessel wall, the outer and inner diameters, the thickness of the wall, and calculated the Wogenworth index (the ratio of wall area to the area of a lumen), the Kernogan index (the ratio of the area of the lumen to the area of the vessel) and the vascular index (the ratio of the wall thickness to the diameter of the lumen). The UTHSCSA Image Tool® software (Video Test - 5.0) was used to measure these morphometric characteristics. The obtained quantitative indicators were processed statistically using the STATISTIKA software package. The reliability of the difference between independent comparable values was determined using the Student and Mann-Whitney criteria. Results and discussions Having analyzed the data of the study, we found that the cross-section area of regular vessels in animals with EDLP increased by 14.22%, the area of the lumen decreased by 4.05%, the outer diameter increased by 7.40%, and the internal diameter decreased by 8.27% compared to similar indicators in the intact group. The thickness of the wall of the studied vessels in conditions of simulated pathology increased by 24.92% compared to the intact group, which is statistically significant. The area of the vessel wall also presented statistically significant growth (20.33%). The Vogenvort index in animals with EDLP did not differ significantly from the similar indicator of the intact group, the Kernogan index decreased by 21.31%, and the vascular index increased by 38.58%. The study of smaller intramural vessels revealed statistically significant change of all morphometric parameters in animals with EDLP compared to the group of intact animals. Thus, the cross-sectional area increased by 35.98%, the area of the vascular lumen decreased by 48.67%, the outer diameter increased by 13.26%, and the internal diameter decreased by 18.29% compared to similar indices of the group consisted of intact animals. The thickness of the wall of smaller arteries in animals with EDLP increased by 42.38%, the area of the wall increased by 51.67% compared to intact animals. The Vogenvort index increased by 76.41%, the vascular index - by 52.65%, and the Kernogan index decreased by 75.12% compared to similar indices of the intact group of experimental animals. Conclusions The morphometric study of the myocardial vessels demonstrated the development of expressed structural rebuild of the arteries, characterized by thickening of the wall and narrowing of the lumen, which leaded to a decrease in coronary artery throughput capacity, complicated blood flow and, as a consequence, ischemia and myocardial dystrophy.